Gestur dan Diam: Komunikasi Nonverbal dalam Membangun Karakter Utama pada Film "Titip Surat untuk Tuhan" - Achmad Zaky Faiz (Pawarta: Journal of Communication and Da'wah, 2025)
This research analyzes the central and fundamental role of nonverbal communication in shaping the main character, Dinda, in the film Titip Surat untuk Tuhan (Entrust a Letter to God). Instead of relying on dialogue, the film predominantly uses physical cues (facial expressions, body movements, eye gaze, and touch) to construct Dinda’s complex inner narrative. The analysis reveals that changes across four nonverbal domains —kinesics (body movements and facial expressions), oculesics (eye gaze), haptics (touch), and proxemics (physical distance) — are crucial in conveying the depth of her emotions and her struggle. Dinda’s shift in kinesics from nimble movements to slower and stiffer motions reflects her physical struggle. The change in her facial expressions from cheerful to melancholy, along with her empty gaze, narrates her emotional journey from hope to peaceful acceptance. Her tight hand-hold (haptics) with her father demonstrates warmth and deep dependence, while her chosen physical distance (proxemics) communicates isolation and a desire to hide her suffering. This study proves that body language is a more powerful and effective storytelling tool for arousing empathy and fostering a deeper understanding of character, thereby establishing nonverbal communication as the core of the film's emotional message.